1994
DOI: 10.1111/j.1525-1470.1994.tb00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Benign Cephalic Histiocytosis: Case Report and Literature Review

Abstract: A 3-year-old boy had maculopapules on his face and neck since age 6 months. These were yellow-brown, asymptomatic, and clinically similar to flat warts. Histopathologic study revealed a fibrohistiocytic infiltrate in the superficial dermis. Ultrastructurally, comma-shaped bodies, desmosome-like junctions, and coated vesicles were seen; there were no lipid droplets or Birbeck granules. With these data, a diagnosis of benign cephalic histiocytosis was made. Twenty-five cases are reported in the literature: 17 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 18 publications
1
5
0
2
Order By: Relevance
“…Benign cephalic histiocytosis (BCH) is an extremely rare form of non‐Langerhans cell histiocytosis in which multiple small yellow to red‐brown papules similar to those in our patient develop initially on the cheeks and forehead, and later involving the whole head, neck, and sometimes upper trunk and arms (8). A recent review of the literature found skin involvement other than head, neck, and shoulders in 16 out of 25 patients, as in our patient (9). The mucous membranes, palms, soles, and viscera are not involved, and serum lipids are normal, as were those of our patient (8).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Benign cephalic histiocytosis (BCH) is an extremely rare form of non‐Langerhans cell histiocytosis in which multiple small yellow to red‐brown papules similar to those in our patient develop initially on the cheeks and forehead, and later involving the whole head, neck, and sometimes upper trunk and arms (8). A recent review of the literature found skin involvement other than head, neck, and shoulders in 16 out of 25 patients, as in our patient (9). The mucous membranes, palms, soles, and viscera are not involved, and serum lipids are normal, as were those of our patient (8).…”
Section: Discussionsupporting
confidence: 80%
“…A complete blood count demonstrated microcytosis and hypochromia [Hb 11.7 g/dL (5, 5–10, 10–13), MCV 66fL (70–86), MCH 22.2 pg (27–32)]. He had a peripheral blood monocytosis (monocytes 1.7 × 10 9 (0.4–1.2)) that had normalized when repeated at age 3 1 / 2 years (1.0 × 10 9/l, normal range 0.7–1.5).…”
Section: Case Reportmentioning
confidence: 99%
“…El diagnóstico diferencial debe establecerse principalmente con las verrugas planas, la urticaria pigmentosa, las HCL y otras HSCL, especialmente con la Histiocitosis cefálica benigna (HCB) [20,21]. Probablemente la mayor dificultad se encuentra en la diferenciación con ésta última, ya que se parecen desde un punto de vista clínico y la histopatología es idéntica a la de la HEG.…”
Section: Discussionunclassified
“…[6][7][8][9] BCH also occurs on the head, but occasionally, as in DJXG, the trunk and upper extremities are involved. 10 Histologically, both these disorders share the same image of diffuse macrophage infiltrates. However, xanthomatization is less prominent in BCH and giant cells are only occasionally encountered.…”
Section: Discussionmentioning
confidence: 99%
“…GEH also usually lacks giant and foamy cells, as is BCH and early JXG. 10 It can precede other forms of NLD, including eruptive JXG, xanthoma disseminatum (XD) and progressive nodular histiocytosis (PNH), or even represent an early manifestation of an indeterminate cell histiocytosis. [12][13][14] GEH apparently represents an early undifferentiated stage of various NLD and should not be considered as a distinct entity.…”
Section: Discussionmentioning
confidence: 99%